Bactericidal Effect of Lysozyme - V. M. Podboronov; M. Yu. Shchelkanov; I. P. Smirnova; L. A. Burenkova; V. P. Novikova; V. A. Aristova; E. L. Novikova; G. G. Moskvitina; A. M. Ioffe (Антибиотики и Химиотерапия)
Isolation of lysozyme from hemolymph of Alveonasus lahorensis (Acari: Parasitiformes, Argasidae) and Hyalomma marginatum (Acari: Parasitiformes, Ixodidae) with using ultrasound is described. It was shown that the bactericidal effect of the ultrasound-extracted lysozyme against Staphylococcus aureus and Micrococcus luteus significantly exceeded that of the chicken egg lysozyme and lysozyme from ticks without ultrasound exposure. Disintegration of the hemolymph cells increased lysozyme production.